2007
DOI: 10.1111/j.1467-9701.2007.01001.x
|View full text |Cite
|
Sign up to set email alerts
|

Macro Determinants of FDI Inflows to Japan: An Analysis of Source Country Characteristics

Abstract: This paper examines the source country determinants of FDI into Japan. The paper highlights certain methodological and theoretical weaknesses in the previous literature and offers some explanations for hitherto ambiguous results. Specifically, the paper highlights the importance of panel data analysis, and the identification of fixed effects in the analysis rather than simply pooling the data. Indeed, we argue that many of the results reported elsewhere are a feature of this mis-specification. To this end, poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 74 publications
0
36
1
1
Order By: Relevance
“…Likewise, in equation (1) G it represent GDP per capita; FDI it is net inward foreign direct investment in current US$, EXPit is exports (trade) and ε it is stochastic term. Moreover, the stochastic term ε it is contained w it which is time invariant and accounts for any not observable singular source country-specific effect which is not included in the econometric model and µ it is supposed to be white noise (Kimino et al 2007;Azam and Ather, 2015). Furthermore, equation (1) states that the impacts of FDI inflows and exports on economic growth are expected to be positive in the study.…”
Section: Econometric Model and Empirical Results Interpretationmentioning
confidence: 99%
“…Likewise, in equation (1) G it represent GDP per capita; FDI it is net inward foreign direct investment in current US$, EXPit is exports (trade) and ε it is stochastic term. Moreover, the stochastic term ε it is contained w it which is time invariant and accounts for any not observable singular source country-specific effect which is not included in the econometric model and µ it is supposed to be white noise (Kimino et al 2007;Azam and Ather, 2015). Furthermore, equation (1) states that the impacts of FDI inflows and exports on economic growth are expected to be positive in the study.…”
Section: Econometric Model and Empirical Results Interpretationmentioning
confidence: 99%
“…High volatility of the exchange rate is associated with more FDI because companies have incentive to diversify their production locations. Kimino et al (2007) examine the determinants of FDI inflows to Japan specifically, and find that some variables that many cross-country studies have found to be important determinants do not influence FDI flows into Japan once source country fixed effects are accounted for. For example, the exchange rate, exchange rate volatility, the borrowing cost differential, and the labor cost differential all lose their power to explain the pattern of FDI inflows (Kimino et al, 2007, Table 3).…”
Section: Determinants Of Fdimentioning
confidence: 99%
“…Kimino et al (2007) examine the determinants of FDI inflows to Japan specifically, and find that some variables that many cross-country studies have found to be important determinants do not influence FDI flows into Japan once source country fixed effects are accounted for. For example, the exchange rate, exchange rate volatility, the borrowing cost differential, and the labor cost differential all lose their power to explain the pattern of FDI inflows (Kimino et al, 2007, Table 3). The only variables that are robust seem to be the gravity model related variables (GDP and distance), exports from the source country, source country risk, and cultural distance.…”
Section: Determinants Of Fdimentioning
confidence: 99%
“…Borenstein et al [5] concluded that, the main channel through which FDI contributed to economic growth was by stimulating technological progress, rather than by increasing total capital accumulation in the host country. In addition, the entry of foreign firms' increases competition in the host country, thereby further stimulating domestic firms to operate more efficiently [3]. Moreover, many studies suggest that the spillover effects of FDI promote host countries' exports by improving the productivity of local firms [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A major reason that developing countries would like to attract direct investment from more advanced countries and get involved in globalisation is potential technology spillovers [2]. Most of these developing countries believe that foreign affiliated firms have higher levels of total factor productivity and it is hoped that foreign affiliated firms would bring superior technologies, new business models, innovative management and marketing know-how to the host country [3,4]. Borenstein et al [5] concluded that, the main channel through which FDI contributed to economic growth was by stimulating technological progress, rather than by increasing total capital accumulation in the host country.…”
Section: Introductionmentioning
confidence: 99%